If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 1) + -3 = 2x + 7 Reorder the terms: 2(1 + 2x) + -3 = 2x + 7 (1 * 2 + 2x * 2) + -3 = 2x + 7 (2 + 4x) + -3 = 2x + 7 Reorder the terms: 2 + -3 + 4x = 2x + 7 Combine like terms: 2 + -3 = -1 -1 + 4x = 2x + 7 Reorder the terms: -1 + 4x = 7 + 2x Solving -1 + 4x = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 4x + -2x = 7 + 2x + -2x Combine like terms: 4x + -2x = 2x -1 + 2x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 2x = 7 + 0 -1 + 2x = 7 Add '1' to each side of the equation. -1 + 1 + 2x = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 7 + 1 2x = 7 + 1 Combine like terms: 7 + 1 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 6x-8=2x+9 | | -6x+147=-2x+135 | | 2(2x-9)=x-9 | | -15=3(2x+7) | | 5(y-2)-7y=-4 | | 30(12)+9=9x | | Sinx*tanx=3*tanx | | 80+70=(2x-6) | | -5=-c-3 | | -8c=-6c+8 | | W/4-3=4 | | lnx+ln(x-6)=ln(6x-35) | | 6/n=8/12 | | 7b-15=5-3 | | 30(12)=9x+9 | | 3k^2+23k-23=0 | | 5-4y=1 | | y=A(x+3)(x-4+5i)(x-4-5i) | | (2x-25)+(2x+17)+(x+13)=180 | | -9x+4=58 | | 5x^2+-19x-4=0 | | 21=-3e | | x^2+-19x-4=0 | | 6-7x=-8 | | 7+7x-4x=10 | | 157-3x=5x+85 | | =49x^2+4 | | 1+4x-6x=-13 | | A=0.5h(c+d) | | -4+3a=5 | | 7y+7=7 | | -81=-7x-3x-1 |